Colletotrichum capsici-Induced Disease Development in Postharvest Pepper Associated with Cell Wall Metabolism and Phenylpropanoid Metabolism - Yunfen Liu; Qian Song; Feilong Yin; Yuanli Liang; Mubo Song; Meiying He; Liang Shuai (Horticulturae)
Colletotrichum capsici is an important pathogen causing anthracnose in postharvest peppers in parts of Asia, seriously compromising quality and storage life. Unveiling the pathogenic mechanism can better prevent postharvest disease in pepper. This study investigated the impacts of C. capsici infection on cell wall and phenylpropanoid metabolism in postharvest pepper. Compared to the non-inoculated peppers, C. capsici infection notably increased the disease index, damaged visual quality, and reduced the firmness. Morphological observations showed that C. capsici infection contributed to the collapse of epidermal cell structure. During the early stage, C. capsici triggered pepper’s defensive responses, including lignin deposition around the wounds, increased cellulose and hemicellulose content, and boosted disease-resistance enzymes, including phenylalanine ammonia-lyase (PAL), cinnamic acid 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), cinnamyl alcohol dehydrogenase (CAD), laccase (LAC), β-1,3-glucanase (β-1,3-Glu), and chitinase (CHI), alongside elevated total phenolics and flavonoids. However, as storage time progressed, the activities of carboxymethy cellulase (Cx), polygalacturonase (PG), pectin methylesterase (PME), and β-glucosidase (β-Glu) remained at a high level, leading to a reduction in cell wall components, a decline in the activities of disease-resistance enzymes, and a decrease in phenylpropanoid metabolite, resulting from disease progression in pepper. These insights highlight the need for early intervention strategies to mitigate postharvest losses by targeting pathogen-induced stress responses and cell wall integrity preservation.